Kanserli hastalara bakım verenlerde yaşam kalitesinin değerlendirilmesi - Karabuğa, Hatice (My University, 2009)
Evaluation of Quality of Life Among Caregivers of Patients with Cancer This study was done to investigate quality of life and factors related to quality of life among 120 caregivers of patients with cancer. The data were collected by means of general information form with patients and their caregivers, The Multidimensional Scale of Perceived Social Support, The MOS 36 Item Short Form Health Survey, Beck Depression Inventory, State/ trait Anxiety Inventory, The Caregiver Quality of Life Index-Cancer (CQOLC) Scale. Collected data were evaluated by SPSS-version 11.5. In this study, first of all, we evaluated reliability and validity of The Caregiver Quality of Life Index-Cancer Scale. The result of cronbach’s alpha and test-retest correlation coefficient, criteria, discriminant and convergent/ divergent validity were satisfactory. Caregivers’ mean quality of life score was quite low. Caregivers who were female, old, had financial difficulties and had difficulties to continue their routine responsibilities or duties and who weren’t supported had lower quality of life scores. Caregivers who took care male patients had lower quality of life scores as well. Caregiving, cancer, quality of life.

Bu çalışma yaşam kalitesinin ve yaşam kalitesini etkileyen faktörlerin değerlendirilmesi amacıyla kanserli hastalara bakım veren 120 aile üyesinde yapıldı. Veriler Hasta ve Bakım Verenleri Tanılama Formu, Çok Boyutlu Algılanan Sosyal Destek Ölçeği, SF-36 Türkçe Yaşam Kalitesi Ölçeği, Beck Depresyon Ölçeği, Sürekli Kaygı Ölçeği ve Kanserli Hastalara Bakım Verenlerde Yaşam Kalitesi Ölçeği ile toplandı, toplanan veriler SPSS 11.5 versiyonu ile değerlendirildi. Mevcut çalışmada güvenirliği-geçerliği yapılan Kanserli Hastalara Bakım Verenlerde Yaşam Kalitesi Ölçeği’nin cronbach’s alpha, test-retest korelasyon katsayısı ile ölçüt, ayırt edici ve yakınlaşım/ uzaklaşım geçerlik bulgularının tatmin edici düzeyde olduğu belirlendi. Çalışmada hasta yakınlarının yaşam kalitesi oldukça düşük idi. Kadın bakım verenlerin, yaşlı olanların, erkek hastaya bakanların, ekonomik durumu kötü olanların, başkalarından destek almayanların ve sorumluluklarını yerine getirmede güçlük yaşayanların yaşam kaliteleri düşük bulundu. Bakım verme, kanser, yaşam kalitesi.
Keywords: Kanser; Yaşam Kalitesi